How do you simplify (-6)^0?

3 Answers
Mar 20, 2016

color(blue)(=1

Explanation:

  • As per property:
    color(blue)(a^0= 1

So, applying the above:

(-6)^0 =1

Mar 20, 2016

1

Explanation:

(-6)^0=(-6)^(n-n)=(-6)^n/(-6)^n=1

Mar 20, 2016

(-6)^0 = 1

Explanation:

If n is a positive integer, then for any number a we can define:

a^n = overbrace(a xx a xx .. xx a)^"n times"

This has the pleasing property that if m and n are positive integers then:

a^m * a^n = overbrace(a xx a xx .. xx a)^"m times" xx overbrace(a xx a xx .. xx a)^"n times"

=overbrace(a xx a xx .. xx a)^"m + n times" = a^(m+n)

If a != 0 then we can also define a^(-n) = 1/underbrace(a xx a xx .. xx a)_"n times"

With this definition we find that a's in numerators and denominators combine or cancel in such a way that:

a^m * a^n = a^(m+n)

for any integers m and n (positive or negative).

In particular. If a != 0 then a^0 = a^(1-1) = a^1 * a^(-1) = a/a = 1

In fact, in the case n=0 we can think of a^0 as being an empty product of 0 copies of a. The empty product has the value 1 - the identity under multiplication.

color(white)()
In particular, if a = -6 then a^0 = 1